Correlation Between Interest Entry Senior High School Student with Parents Social Economy and Environment (Case Study: Senior High School Students in Manado City) - Djoni Hatidja (Sam Ratulangi University, 2008)
The objective of this research was to know correlation between interest entry of senior high school student at university with parents social economy, and stay location. This research had been done at some state senior high school (third natural science class, third social science class and third language class) in Manado on January to April 2007. The results showed that parents education, parents job, parents income and environment of student address have correlation between interest student to continu at university. Keywords: Senior high school, parents education, parents income